Penerapan Model Discovery Learning untuk Meningkatan Kemampuan Berpikir Kritis Siswa - Noufal Akbari Harahap; Titin Setiawati (Jurnal Pendidikan Indonesia, 2022)
The high number of traffic accidents on the highway, precisely in the city of Medan, is a factor in the death of children aged 14-23 years. One of them is the lack of attention and education of parents about traffic sign. In this board game design, the aim is to learn the rules of traffic signs for children aged 7-11 years. In the design of this game, there is a board game that contains various information about traffic sign and road markings. This game will produce games that are no less exciting and add a lot if insight to children and teenagers who want to know the rules of traffic signs in it.